Never heard that before! Interventional strategies to improve anatomical knowledge retention in nursing students - Narnaware, Yuwaraj; Neumeier, Melanie (My University, 2021)
Background: Nursing students perceive anatomy & physiology as anxiety provoking & stressful subjects. They experience difficulty to acquire, transfer, retain and confidently apply bioscience knowledge to subsequent years of nursing education. In sufficient bioscience knowledge can result in nursing errors. Nursing students are unable to put bioscience knowledge into practice. Objectives: To evaluate knowledge acquisition in first year & its retention and application in the second year. Identify factors affecting knowledge acquisition, retention, and application. Discuss experiential learning strategies to improve knowledge retention. Design your own project to identify knowledge gaps and appropriate learning and retention strategies.
Keywords: knowledge retention; nursing students